It is known that a b = 1 0 9 1 7 3 + 1 0 8 2 + 9 9 1 0 where a , b > 1 are positive integers. What is the value of a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wonderful!
1 0 9 ⋅ a b = 1 7 3 + 1 0 8 2 + 9 9 1 0
1 7 3 + 1 0 8 2 + 9 9 1 0 = ( 1 8 − 1 ) 3 + ( 2 2 ⋅ 3 3 ) 2 + 9 9 0 9 + 1 = ( 2 ⋅ 3 2 − 1 ) 3 + 2 4 ⋅ 3 6 + 3 6 7 ⋅ 3 3 + 1 = 2 3 ⋅ 3 6 − 3 ⋅ 2 2 ⋅ 3 4 + 3 ⋅ 2 ⋅ 3 2 − 1 + 2 4 ⋅ 3 6 + 3 6 7 ⋅ 3 3 + 1 = ( 2 3 + 2 4 ) 3 6 − 2 2 ⋅ 3 5 + ( 2 + 3 6 7 ) 3 3 = ( 2 4 × 3 ) 3 5 − 4 ⋅ 3 5 + ( 4 1 × 3 2 ) 3 3 = ( 7 2 − 4 + 4 1 ) 3 5 = 1 0 9 ⋅ 3 5
∴ a = 3 , b = 5 , a + b = 3 + 5 = 8
1 7 3 + 1 0 8 2 + 9 9 1 0 = 4 9 1 3 + 1 1 6 6 4 + 9 9 1 0 = 2 6 4 8 7
1 0 9 2 6 4 8 7 = 2 4 3
2 4 3 / 2 / 2 / 2 / 2 / 2 / 2 / 2 / 2 = 2 8 = 0 . 9 4 9 …
2 4 3 / 3 / 3 / 3 / 3 / 3 = 3 5 = 1
3 + 5 = 8
*Author’s Notes*:
All calculations were done on a calculator except for the last one
All of this is L a T e X ed
Problem Loading...
Note Loading...
Set Loading...
Note that 9 9 1 0 = 1 0 4 − 3 4 − 2 3 − 1 , hence using the factorizations of a 3 − b 3 and a 2 − b 2 , we have 1 7 3 + 1 0 8 2 + 9 9 1 0 = 1 7 3 + 1 0 8 2 + 1 0 4 − 3 4 − 2 3 − 1 = ( 1 7 3 − 2 3 ) + ( 1 0 8 2 − 1 ) + ( 1 0 4 − 3 4 ) = ( 1 7 − 2 ) ( 1 7 2 + 1 7 ⋅ 2 + 2 2 ) + ( 1 0 8 − 1 ) ( 1 0 8 + 1 ) + ( 1 0 2 − 3 2 ) ( 1 0 2 + 3 2 ) = ( 1 5 ) ( 3 2 7 ) + ( 1 0 7 ) ( 1 0 9 ) + ( 9 1 ) ( 1 0 9 ) = 1 0 9 ( 1 5 ⋅ 3 + 1 0 7 + 9 1 ) = 1 0 9 ⋅ 2 4 3 = 3 5 ⋅ 1 0 9 Thus, 1 0 9 1 7 3 + 1 0 8 2 + 9 9 1 0 = 3 5 , so a = 3 and b = 5 , making the answer a + b = 3 + 5 = 8 .